2010
DOI: 10.1007/s10552-010-9520-y
|View full text |Cite
|
Sign up to set email alerts
|

Body size and risk of prostate cancer in Jamaican men

Abstract: We investigated the associations between body size and risk of prostate cancer in a hospital-based case-control study in Jamaica. Height, weight, waist, and hip circumference were measured at enrollment, and data collected on medical and lifestyle factors for newly diagnosed cases (n = 243) and controls (n = 275). Compared with men in the normal range of waist-hip ratio (WHR), men with WHR > or =0.95 were at greater risk of total prostate cancer (OR,1.72; CI, 1.01-3.00) and high-grade cancer (OR, 2.02; CI, 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
5
17
0
Order By: Relevance
“…Those in the highest quartile of waist circumference (!108 cm) with a family history had a 2-fold increased risk of disease compared with those with waist circumference <0.95 (OR, 2.12; 95% CI, 1.10-4.11), whereas men without such history were not found to be at elevated risk. Two additional studies reported the association only among cases with aggressive or advanced disease (16,17), whereas a third investigation reported that higher waist circumference was associated with increased risk only after adjustment for BMI (11).…”
Section: Waist Circumferencementioning
confidence: 99%
See 4 more Smart Citations
“…Those in the highest quartile of waist circumference (!108 cm) with a family history had a 2-fold increased risk of disease compared with those with waist circumference <0.95 (OR, 2.12; 95% CI, 1.10-4.11), whereas men without such history were not found to be at elevated risk. Two additional studies reported the association only among cases with aggressive or advanced disease (16,17), whereas a third investigation reported that higher waist circumference was associated with increased risk only after adjustment for BMI (11).…”
Section: Waist Circumferencementioning
confidence: 99%
“…Several studies have indicated that WHR does not influence the development of prostate cancer (8, 9, 15, 16, 19 22, 23, 24), whereas others report a significant positive association (11,13,17,21). Although some investigations support the relationship between higher WHR measurements and increased prostate cancer risk regardless of disease severity, the association has been shown to be stronger among those with advanced, high-grade disease (13,17).…”
Section: Waist To Hip Ratiomentioning
confidence: 99%
See 3 more Smart Citations